Levan as a Bioactive Material for Medical Applications - (:unkn) unknown (CAISTER ACADEMIC PRESS, 2019)
Levan is a fructan homopolymer with beta-(2, 6) glycosidic bonds between its fructose monomers and can be obtained from plants and numerous microorganisms. This extracellular polysaccharide distinguishes from other natural polysaccharides with its unique properties and hence, its wide range of possible applications have been studied thoroughly in the past decade resulting with interesting findings related to its wound healing, heparin-mimetic, anticancer, anti-inflammatory, antiviral, non-toxic, antihyperlipidemic, hypocholesterolemic, hyperglycaemic inhibitory and anti-AIDS properties. Besides medical properties, it is also digestible by human gastrointestinal (GI) tract and shows prebiotic activity allowing it to be used in functional foods. This chapter will mainly focus on levan polysaccharide and its medical applications such as bioactive carrier in drug delivery systems and bioactive surfaces produced by laser technologies.
Keywords: ACTIVITIES IN-VITRO; ANTIOXIDANT ACTIVITIES; HALOMONAS-SMYRNENSIS; ANTITUMOR ACTIVITIES; OXIDATIVE STRESS; MULTILAYER FILMS; MICROBIAL LEVAN; SULFATED LEVAN; POLYSACCHARIDE; EXOPOLYSACCHARIDE